Pengaruh Kualitas Produk dan Citra Merek Terhadap Kesadaran Merek Produk Madu Herbal Zymuno di Kota Makassar - Ilma Wulansari Hasdiansa; Sitti Hasbiah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of product quality and brand image on brand awareness of Zymuno herbal honey products in Makassar City. This study uses a quantitative approach with an associative research type. Data were collected using a survey through a questionnaire distributed to 100 respondents with a purposive sampling technique. The analysis method used is multiple linear regression, accompanied by F test, t test, and determination coefficient analysis. The results of the study indicate that product quality and brand image simultaneously have a significant effect on brand awareness. Partially, each variable also shows a significant effect. The determination coefficient value of 74.5% indicates that variations in brand awareness can be explained by the two independent variables. These findings provide practical recommendations in designing marketing strategies for local herbal products.